2019
DOI: 10.1159/000504834
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Patients with High National Institutes of Health Stroke Scale as Thrombectomy Candidates Using the Kentucky Appalachian Stroke Registry

Abstract: Introduction: Mechanical thrombectomy has become standard of care for emergent large vessel occlusive stroke. Estimates of incidence for thrombectomy eligibility vary significantly. National Institutes of Health Stroke Scale (NIHSS) of 10 or greater is highly predictive of large vessel occlusion. Using our Kentucky Appalachian Stroke Registry (KApSR), we evaluated temporal trends in stroke admissions with NIHSS ≥10 to determine patient characteristics among that group along with effects and needs in thrombecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, other studies revealed that compared to relative male patients with acute anterior circulation stroke, female patients exhibited poorer prognosis after recanalization [48]. Previous reports indicate that key factors, including gender differences in risk factors and types and proportions of ischemic stroke complications, lead to asymmetry in clinical outcomes between male and female patients [49]. Most male patients have a history of smoking and drinking and are prone to CAD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, other studies revealed that compared to relative male patients with acute anterior circulation stroke, female patients exhibited poorer prognosis after recanalization [48]. Previous reports indicate that key factors, including gender differences in risk factors and types and proportions of ischemic stroke complications, lead to asymmetry in clinical outcomes between male and female patients [49]. Most male patients have a history of smoking and drinking and are prone to CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Most male patients have a history of smoking and drinking and are prone to CAD. Female patients are exposed to other risk factors, including obesity, hypertension, atrial fibrillation, and venerable age [49, 50]. In addition, many factors that cannot be evaluated rapidly, such as weakness, musculoskeletal function, neurological dysfunction, and social psychological status before stroke, may also adversely affect prognosis in females [51, 52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An NIHSS ≥10 was identified as the most balanced threshold to predict LVO with a sensitivity of 73% and specificity of 74% ( 9 ). Thus, the NIHSS score is a frequently used prediction instrument for LVO ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…An NIHSS ≥10 was identified as the most balanced threshold to predict LVO with a sensitivity of 73% and specificity of 74% (9). Thus, the NIHSS score is a frequently used prediction instrument for LVO (28,29). Secondly, ∼15.9% of the patients with AIS were excluded from the analysis because the NIHSS score at admission was missing.…”
Section: Limitationsmentioning
confidence: 99%